Elementary and macroscopic light-induced currents and their Ca2+-dependence in the photoreceptors of Periplaneta americana - Immonen, Esa-Ville; Krause, Stephan; Krause, Yani; Frolov, Roman; Vähäsöyrinki, Mikko T.; Weckström, Matti (Frontiers in Physiology, 2014)
In a microvillar photoreceptor, absorption of an incident photon initiates a phototransduction reaction that generates a depolarizing light-induced current in the microvillus. Although in-depth knowledge about these processes in photoreceptors of the fruitfly Drosophila is available, not much is known about their nature in other insect species. Here, we present description of some basic properties of both elementary and macroscopic light-induced currents and their Ca2+-dependence in the photoreceptors of a dark-active species, the cockroach Periplaneta americana. Cockroach photoreceptors respond to single photon absorptions by generating quantum bumps with about 5-fold larger amplitudes than in Drosophila. At the macroscopic current level, cockroach photoreceptors responded to light with variable sensitivity and current waveform. This variability could be partially attributed to differences in whole-cell capacitance. Transient light-induced currents, both elementary and macroscopic, showed only moderate dependence on extracellular Ca2+. However, with long light pulses, response inactivation was largely abolished and the overall size of light-induced currents increased when extracellular Ca2+ was omitted. Finally, by determining relative ionic permeabilities from reversals of light-induced currents, we demonstrate that when compared to Drosophila, cockroach light-gated channels are only moderately Ca2+-selective.